Researching Chinese Learners
XIX, 321 p.
Keywords: This collection focuses on Chinese learners with original data sets using innovative research methods. It investigates Chinese learners' learning and language skills, perceptions and particularly the processes of reciprocal intercultural adaptations in a wide international context of Australia, Canada, China, Hong Kong, New Zealand and the UK.